2007
DOI: 10.1002/jrs.1835
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of smithsonite

Abstract: Raman spectroscopy at both 298 and 77 K has been used to study a series of selected natural smithsonites from different origins. An intense sharp band at 1092 cm −1 is assigned to the CO 3 2− symmetric stretching vibration. Impurities of hydrozincite are identified by a band around 1060 cm −1 . An additional band at 1088 cm −1 which is observed in the 298 K spectra but not in the 77 K spectra is attributed to a CO 3 2− hot band. Raman spectra of smithsonite show a single band in the 1405-1409 cm −1 range assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 20 publications
2
27
0
1
Order By: Relevance
“…With regard to the iron hydroxycarbonate, on both samples the main peak is at 1070 cm −1 and it can be assigned to the C-O symmetric stretching vibration (ν 1 ). [24,25,34,35] The weak shift observed on the band at 1510 cm −1 when both spectra are compared shows that it cannot be assigned to the hydroxyl group of the crystalline structure. In the case of the copper hydroxycarbonate such as azurite and malachite, it has been suggested that the peaks between 1400 and 1520 cm −1 are due to the carbonate (ν 3 ) antisymmetric stretching vibration.…”
Section: Chukanovite and D-chukanovite Reference Powdersmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the iron hydroxycarbonate, on both samples the main peak is at 1070 cm −1 and it can be assigned to the C-O symmetric stretching vibration (ν 1 ). [24,25,34,35] The weak shift observed on the band at 1510 cm −1 when both spectra are compared shows that it cannot be assigned to the hydroxyl group of the crystalline structure. In the case of the copper hydroxycarbonate such as azurite and malachite, it has been suggested that the peaks between 1400 and 1520 cm −1 are due to the carbonate (ν 3 ) antisymmetric stretching vibration.…”
Section: Chukanovite and D-chukanovite Reference Powdersmentioning
confidence: 99%
“…The 730 cm −1 band could be correlated to a (ν 4 ) O-C-O asymmetric bending. [25,34,35] The bands present between 100 and 500 cm −1 are hardly mentioned in the literature. According to Frost [36] on their study on malachite, there are too many bands in comparison to those predicted by factor group analysis.…”
Section: Chukanovite and D-chukanovite Reference Powdersmentioning
confidence: 99%
“…5). The vibration energies of smithsonite were fully assigned by Frost et al (2008) ) in O -Zn -O bending modes in the smithsonite lattice. Therefore, the similarity of the activation energy in the process of temperature quenching and lattice vibration energy indicates that the temperature quenching energy might be transferred as a phonon to the specific lattice vibration through non -radiative transition.…”
Section: Resultsmentioning
confidence: 99%
“…Such studies are compiled here for the following molecules: 1H-and 3H-imidazo [4,5-b]pyridine and their methyl derivatives, [113] copper(II) chloride and bromide compounds of KCuBr 3 , [114] 5,6-diméthyluracile, [115] [C(NH 2 ) 3 ] 2 M II (H 2 O) 4 (SO 4 ) 2 , M II = Mn, Cd and VO, [116] potassium trimethylsilanolate, [117] 2-aminopyridinium-4-hydroxybenzenosulfonate, [118] the H 4 I 2 O 10 2− ion in CuH 4 I 2 O 10 · 6H 2 O, [119] 2-amino-4,6-dihydroxypyrimidine, [120] 3 (or 4 or 6)-methyl-5-nitro-2-pyridinethiones, [121] 2-methyl-4-nitroaniline (MNA) crystal, [122] 2-amino-5-chloropyridinium hydrogen selenate, [123] the food dye amaranth, [124] transstilbene in the excited singlet state, [125] chloramphenicol, [126] oroxylin, [127] 4-fluoro-N-(2-hydroxy-4-nitrophenyl)benzamide, [128] phenanthridine, [129] 3,5 dichloro hydroxy benzaldehyde and 2,4 dichloro benzaldehyde. [130] Solid State (Minerals, Crystals, Linear Chains, Glasses, Ceramics and Disordered Materials) Minerals A great number of minerals have been studied during 2008 by the Frost group [131 -146] using both Raman and infrared spectroscopies: smithsonite, [131] the uranyl carbonate mineral voglite, [132] hydrotalcite with CO 3 2− and (MoO 4 ) 2− anions in the interlayer, [133] the uranyl phosphate minerals phosphuranylite and yingjiangite, [134] the uranyl carbonate mineral zellerite, [135] the molybdate-containing uranyl mineral calcurmolite, [136] the oxalate mineral wheatleyite Na 2 Cu 2+ (C 2 O 4 ) 2 ·2H 2 O, [137] the nickel silicate mineral pecoraite, [138] synthetic nesquehonite, [139] the uranyl mineral, compreignacite, K 2 [(UO 2 ) 3 O 2 (OH) 3 ] 2 ·7H 2 O, [140] the hydroxy nickel carbonate minerals nullaginite and zaratite, [141] schmiederite Pb 2 Cu 2 [(OH) 4 |S...…”
Section: Vibrational Studies In Chemistry (Combined Raman Infrared mentioning
confidence: 99%